Metástasis cutáneas de carcinomas primarios de origen desconocido. Aporte de 3 casos y breve revisión [Cutaneous metastases from primary carcinomas of unknown origin. Contribution with3 cases and brief review] - Silvia Mancía; Beatríz Di Martino Ortiz; Tatiana Moreno; Lourdes Rodríguez; Romina Contreras; Julio Recalde; Mirtha Rodríguez; Oilda Knopfelmacher; Lourdes Bolla de Lezcano; Hugo Boggino (Our Dermatology Online, 2015)
Metastases of unknown primary site occurs in about 5-10% of patients diagnosed with cancer. Usually appear after diagnosis of the primary cancer, but may be the first clinical sign of a tumor of unknown origin or the first sign of relapse of cancer. Cancer treatment is based on the recognition of the primary neoplasm, which raise diagnostic and therapeutic challenges. Skin biopsy should be considered in newly emerging lesions in cancer patients in addition to those lesions of sudden onset that are slow to heal, prone to bleeding or vascular appearance, that are not resolved with appropriate treatment. We present three cases of cutaneous metastases as the first manifestation, from which the primary tumor was found.